Correction: Mutant JAK3 phosphoproteomic profiling predicts synergism between JAK3 inhibitors and MEK/BCL2 inhibitors for the treatment of T-cell acute lymphoblastic leukemia. Issue 12 (December 2018) - Degryse, S.; Bock, C.; Demeyer, S.; Govaerts, I.; Bornschein, S.; Verbeke, D.; Jacobs, K.; Binos, S.; Skerrett-Byrne, D.; Murray, H.; Verrills, N.; Vlierberghe, P.; et al.
Following the publication of this article the authors noted that data describing precisely where phosphorylation sites in proteins modulated following JAK1 or JAK3 inhibition in mutant T-ALL samples was not clearly annotated. Therefore an additional sheet has been added to Supplementary Table 2.